Application of Semantic-Social Technologies in Digital Libraries: A Model Based on Wisdom and Expertise - Mehdi Pazhouhan; Najla Hariri; Yaghoub Norouzi; Fahimeh BabolHavaeji (کتابداری و اطلاع‌رسانی, 2024)
Objective: The purpose of this study is to design a conceptual model for the application of semantic-social technology in digital libraries in Iran. Methodology: This applied research was conducted using Delphi and analytical survey methods. The tool used was a researcher-made questionnaire, which included three parts: the structure of semantic-social technology architecture, semantic-social technology tools, and the function of semantic-social technology. Descriptive statistics, structural equation modeling and partial least squares modeling (PLS-SEM) were used to analyze the statistical data. Findings: In the final research model, most items had a high factor loading and in the main components of the research, including the architecture structure of semantic-social technology, tools of semantic-social technology and the function of semantic-social technology, important items from the perspective of the research community were identified. Accordingly, in the architectural structure of semantic-social technology, the use of RDF schema to describe and describe RDF-based resources, the use of SIOC technology to link blogs, forums and mailing lists had the highest factor loading. Also, in the part of semantic-social technology tools, in the final conceptual model research, video mashups and map mashups had a higher factor loading than others. In the functional part of semantic-social technology, using the URL standard to identify and locate a resource in digital libraries and retrieval function, using RDF tools and using Sub and Super techniques between concepts to retrieve information faster has the highest factor loading. Moreover, in the parts of data and resources and content, the use of RDF tools to exploit multimedia and non-textual resources due to the diversity of available information and in the function of organization and storage, the use of ontology to manage digital resources had higher factor loading. In addition, in the interaction function, the items of communication between the chain of information producers, collectors and users through social semantic web tools had the highest amount of factor loading. Concusion: Considering the results obtained in the proposed model of this research and the items that have gained a high factor loading in the proposed conceptual model, shows that in semantic-social technology in digital library software, what makes this technology progress and success is the correct creation of digital library software. The basis of digital library standards, attention to the XML markup language, Dublin Core, etc. and its integration with semantic tools such as Web 2.0, hashtags and folksonomy, metadata, etc. in line with social technologies such as social networks, mashups, etc.